Lubavitcher women in America : identity and activism in the postwar era - Morris, Bonnie J., 1961- (State University of New York Press, 1998)
Annotation Lubavitcher Women in America offers a rare look at the world of Hasidic women activists since World War II. The revival of ultra-Orthodox Judaism in the second half of the twentieth century has baffled many assimilated American Jews, especially those Jewish feminists hostile to Orthodox interpretations of women's roles. This text gives voice to the lives of those Hasidic women who served the late Lubavitcher Rebbe as educators and outreach activists, and examines their often successful efforts to recruit other Jewish women to the Lubavitcher community in Crown Heights, Brooklyn. Central to this book is how Lubavitcher women have "talked back" to American feminist thought. Arguing that American feminism cannot liberate Jewish women -- that a specifically Jewish spirituality is more appropriate and fulfilling -- Lubavitcher women have helped to swell the ranks of their Rebbe's followers by aggressively promoting the appeal of traditional, structured Jewish observance. The book thus offers a unique look at female anti-feminist religious rhetoric, articulately presented by Jewish "fundamentalists".
Keywords: Women in Judaism -- United States.; Habad -- United States.; Jewish women -- Religious life -- United States.; Crown Heights (New York, N.Y.) -- Religious life and customs.; Femmes dans le judaïsme -- États-Unis.; Habad -- États-Unis.; Juives -- Vie religieuse -- États-Unis.; SOCIAL SCIENCE.; Women's Studies.; RELIGION -- Judaism -- General.; Habad; Jewish women -- Religious life; Women in Judaism; New York (State) -- New York -- Crown Heights; United States